2011
DOI: 10.1242/jcs.077503
|View full text |Cite
|
Sign up to set email alerts
|

Serine/threonine protein kinase SGK1 in glucocorticoid-dependent transdifferentiation of pancreatic acinar cells to hepatocytes

Abstract: Elevated glucocorticoid levels result in the transdifferentiation of pancreatic acinar cells into hepatocytes through a process that requires a transient repression of WNT signalling upstream of the induction of C/EBP-β. However, the mechanism by which glucocorticoid interacts with WNT signalling is unknown. A screen of microarray data showed that the serine/threonine protein kinase SGK1 (serum- and glucocorticoid-regulated kinase 1) was markedly induced in the model B-13 pancreatic rat acinar cell line after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Previous experience with rat B-13 cells has demonstrated that the hepatocyte-like B-13/H cells derived therefrom show good comparability with primary rat hepatocytes with respect to several cytochrome P450s and sensitivities to drug/chemical toxicity [8][9][10][12][13][14]. Exposing HPAC cells to glucocorticoid had a variety of effects also observed when B-13 cells were treated with glucocorticoid, including an inhibition in proliferation, phenotypic changes and low level expression 7 of a variety of hepatocyte-specific transcripts (e.g.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous experience with rat B-13 cells has demonstrated that the hepatocyte-like B-13/H cells derived therefrom show good comparability with primary rat hepatocytes with respect to several cytochrome P450s and sensitivities to drug/chemical toxicity [8][9][10][12][13][14]. Exposing HPAC cells to glucocorticoid had a variety of effects also observed when B-13 cells were treated with glucocorticoid, including an inhibition in proliferation, phenotypic changes and low level expression 7 of a variety of hepatocyte-specific transcripts (e.g.…”
Section: Resultsmentioning
confidence: 98%
“…RNA and protein extracts were prepared and RT-PCR performed as previously outlined [13,14] using primers described in Table 1. Western blotting, immunocytochemistry and immunohistochemistry were performed as described [13,14].…”
Section: Gene Expression Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, B-13 cells do not require an extensive array of recombinant growth factors and/or other signalling inhibitor treatments to direct them to become hepatocytes. Exposure to a single glucocorticoid hormone is all that is required ( Shen et al, 2000 , Wallace et al, 2011 ). Critically, in contrast to stem cell-derived hepatocyte-like cells which generally only form a foetal level of hepatic differentiation, B-13/H cells express many adult hepatocyte genes at adult hepatocyte levels ( Marek et al, 2003 , Fairhall et al, 2013a , Fairhall et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%